STRATEGI KOMUNIKASI CONCEPT PLUS DALAM MEMPROMOSIKAN KOMUNITAS PECINTA HEWAN DI PEKANBARU - Febri Arianto Djufri; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
In the process of animal preservation, some parties have the initiative to create an association or community that protects and conserves animals. This community needs a place for them to socialize and promote animal conservation. Concept Plus Orginizer is Event Organizer which aims to promote animal lovers community in Pekanbaru. This descriptive study used a qualitative approach in which researchers only describe the situations or events without explaining relationships and testing hypotheses or make a prediction. The subject of this study isthe leader and employees of Concept Plus Orginizer, community members, animal lovers, and the general public in Pekanbaru selected using purposive sampling. The object of this study is the communication strategy used by Concept Plus Organizer in sosializing the existence of community of animal lovers in Pekanbaru. Data were collected through interviews, observation, and documentation. The results showed that the audience analysis conducted by Concept Plus effect on the amount of communities registered and the audience attended. Concept Plus uses persuasive communication process in attracting community of animal lovers in Pekanbaru. Messaging strategies used by Concept Plus are printing and electronic media showing quite effective results at attracting public to participate in their community events they organized. Redundancy methods, by influencing the public by repeating the message to the audience, and the method of persuasion, by persuading the community of animal lovers with frequent communication and discussion are also used by Concept Plus to improve the existence of a community of animal lovers in Pekanbaru. Using printing media such as flyers and social media is one of the strategies used by Concept Plus to promote the community of animal lovers in PekanbaruKeyword : Communuication Strategy of Concept Plus Organizer in Promoting The Community of Animal Lovers in Pekanbaru